Vertical integration in the concept of value chains - Rezkin, Petr E. (Journal of the Belarusian State University. Economics, 2021)
The article is devoted to the modern dynamically developing concept of value chain management. The goal of value chain management is to build business processes in distributed production systems (business systems) that produce final products, aimed both at ensuring the financial stability and competitiveness of participating enterprises, and at the economic development of the regions where they are based, including the national economy. The study examines the main approaches to managing value chains (marketing, network, international division of labour). The author proposed several options for general management decisions, studied the types and forms of vertical integration, highlighted the main strategies of vertical integration: «the lower road to competitiveness», «high road to competitiveness», identified and systematised advantages and disadvantages of vertically integrated structures.